Mechanistic Basis and Research Progress of Spleen-Oriented Therapy for Sjögren’s Syndrome Based on the Gut Microbiota-Metabolite-Th17/Treg Axis - Jiang, Ruixin; Gong, Zhengdong; Wang, Jixia (Journal of Contemporary Medical Practice, 2026)
Sjögren’s syndrome (SS), particularly primary Sjögren’s syndrome (pSS), is a chronic autoimmune epithelitis characterized by xerostomia, xerophthalmia, lymphocytic infiltration of the exocrine glands, and systemic immune dysregulation. Accumulating evidence indicates that gut microbiota dysbiosis, altered microbial metabolites, intestinal barrier dysfunction, and T-helper 17/regulatory T-cell (Th17/Treg) imbalance are important contributors to disease initiation and progression, although causal relationships still require further confirmation. In traditional Chinese medicine (TCM), SS has long been discussed within the scope of dryness-related disorders. A spleen-oriented interpretation emphasizes impaired transformation and transportation of fluids as an internal basis for persistent dryness and proposes that spleen dysfunction may be linked to modern concepts of gut microecology, mucosal immunity, and metabolic homeostasis. This review summarizes verified clinical, experimental, and multi-omics evidence concerning the gut microbiota- metabolite-Th17/Treg axis in SS and discusses how selected TCM interventions, including modified Zengye Decoction, FuFang Runzaoling, Lushi Runzao Decoction, Qihuang Jianpi Zishen granules, Shaoyao Gancao Decoction, total glucosides of paeony, Dendrobium and Ophiopogon polysaccharides, and Astragalus-Salvia/Ophiopogon-Dendrobium herb pairs, may modulate inflammation, salivary gland injury, gut microbial composition, and related metabolic pathways. Based on the currently available evidence, a chained pathogenesis model is proposed: spleen deficiency, gut microbial and metabolic disorder, intestinal barrier injury, Th17/Treg imbalance, exocrine gland inflammation, and intermingling of dryness and blood stasis. This model may help connect TCM syndrome differentiation with modern immunometabolic mechanisms and support more precise research on TCM-based SS interventions.